Housing Molecularly Imprinted Polymer Nanoparticles in Polyvinylpyrrolidone/Multiwall Carbon Nanotube Nanofibers to Detect Chiral Terpene Vapors - Fabricio N. Molinari; Fabrizio De Cesare; Antonella Macagnano (Proceedings)
This study proposes a two-step process to design a chiral sensor combining MIP (molecularly imprinted polymer) and electrospinning technologies. First, stereoselective S(-)-limonene molecularly imprinted polymer nanoparticles (MINPs) were fabricated and dispersed into polyvinylpyrrolidone–carbon nanotube (PVP-MWCNT) conductive nanofibers to cover resistive interdigitated electrodes (IDEs). The electrical and sensing performances of the resulting sensor confirmed its capacity to discriminate and quantify the two limonene enantiomers. The sensor’s response to terpene gases appeared completely reversible, probably due to the peculiarity of the nanostructure. The sensor characteristics were influenced by the polymer matrix’s composition ratio, the cavity shape and the interfaces with carbon nanotubes. The morphological properties of the nanofibers were investigated by microscopy (optical, SEM, TEM and AFM).